(untitled) (World Bulletin of Education and Learning, 2025)
In this article, the effectiveness of lessons organized on the basis of socio-emotional education (SEL) is analyzed based on the results of experimental work. The study was conducted with students of the primary education program, in which the influence of SEL elements on the socio-emotional skills of students, their activity in the lesson process, and motivation for learning was studied. Observation, interviews, questionnaires, and diagnostic tasks were used in the experimental process. The obtained results confirmed that lessons based on SEL approaches have a positive impact on the development of empathy, self-awareness, teamwork, and responsible decision-making skills in students. The article provides scientific and practical conclusions on the introduction of SEL technologies into the practice of higher education.